A carbon-dot-based dual-emission probe for ultrasensitive visual detection of copper ions. (15th November 2018) - Kuang, Yunsuo; Chen, Linfeng; Lu, Jiahui; Tian, Xike; Yang, Chao; Li, Yong; Lu, Liqiang; Nie, Yulun
Abstract : In this work, we successfully developed an ultrasensitive dual-emission fluorescent sensor (CRB) for instant visual determination of Cu 2+ by modifying a Cu-sensitive rhodamine B derivative (RB) onto photostable carboxyl modified carbon dots (CDs). Abstract : In this work, we successfully developed an ultrasensitive dual-emission fluorescent sensor (CRB) for instant visual determination of Cu 2+ by modifying a Cu-sensitive rhodamine B derivative (RB) onto photostable carboxyl modified carbon dots (CDs). The RB moiety of the CRB was extremely sensitive to Cu 2+ and exhibited significant orange fluorescence in 1 second, while the blue CD moiety was stable to Cu 2+ . As a result, significant fluorescent color transformation from blue to orange could be observed in the presence of Cu 2+, which could be applied to rapid visualization of Cu 2+ . The CRB exhibited good selectivity and excellent sensitivity to Cu 2+, and the detection limit (LOD) was estimated to be 2 ppb. Moreover, a portable test strip has been successfully developed and applied for the visual inspection of Cu 2+, which provides a convenient and reliable approach to monitor Cu 2+ on site without resorting to instrumental analysis.